Associations between concentrations of perfluoroalkyl substances in human plasma and maternal, infant, and home characteristics in Winnipeg, Canada. (June 2019) - Workman, Clare E.; Becker, Allan B.; Azad, Meghan B.; Moraes, Theo J.; Mandhane, Piush J.; Turvey, Stuart E.; Subbarao, Padmaja; Brook, Jeffrey R.; Sears, Malcolm R.; Wong, Charles S.
Abstract: Perfluoroalkyl substances (PFASs) are known to be toxic, bioaccumulative, and persistent. However, exposure routes and toxic effects to humans are still widely unknown. Our objectives were to evaluate potential correlations between concentrations of PFASs in maternal plasma and infant cord blood with home characteristics and developmental effects, including wheezing. The concentrations of 17 PFASs were measured in plasma from prenatal women (n = 414), postnatal women (n = 247), and cord blood (n = 50) from a subset of participants in a population-based birth cohort in Winnipeg, Manitoba, Canada, using online solid phase extraction (SPE) with liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Multiple linear regression and principal component analysis (PCA) were used to evaluate possible associations with PFAS concentrations. Surveys were used to collect information regarding maternal characteristics (e.g. age, parity, duration of breastfeeding), infant characteristics (e.g. birth weight, birth length, head circumference, gestational age, and incidence of recurrent wheezing), and home characteristics (e.g. home age, carpet coverage in the most used room, presence of new furniture, or recent home renovations). PFASs in plasma were associated with maternal characteristics but not home characteristics or early childhood wheezing. PFASs were not associated with developmental effects, with the exception that perfluoroundecanoic acid (PFUA) was negatively associated with birth weight. Further studies investigating the potential influences of PFUA on birth weight are warranted. Graphical abstract: Image 1 Highlights: PFASs in pre- and postnatal blood were associated with maternal characteristics. PFASs in pre- and postnatal blood were not associated with home characteristics. Perfluoroundecanoic acid (PFUA) was negatively associated with birth weight. No correlations between PFASs in blood and incidence of recurrent wheeze in infants. Perfluoropentanoic acid (PFPA) was among the higher measuring analytes in blood. Abstract : Principal component analysis showed that PFASs in maternal blood were related to maternal characteristics and, for the most part, not home characteristics or developmental effects.